Proposed Site-Specific Response Spectra for Surabaya-Madura Bridge - Masyhur Irsyam; Donny T. Dangkua; Hendriyawan Hendriyawan; R. Bambang Boediono; Dyah Kusumastuti; Engkon K. Kertapati (Civil Engineering Dimension, 2008)
This paper presents a site-specific seismic hazard study to determine the recommended seismic design criteria for Suramadu Bridge. The study is performed using probabilistic seismic hazard approach to determine maximum acceleration and response spectra at bedrock and followed by local site effect analysis to determine maximum acceleration and response spectra at ground surface. The probabilistic seismic hazard analysis (PSHA) is carried out using 3-dimension (3-D) seismic source models (fault source model). Two hazard levels are analysed to represent 150 and 3,300 years return period of ground motion around site location. The local site effect analysis is performed using 1-dimension (1-D) shear wave propagation theory to obtain peak ground acceleration and response spectra at ground surface. Finally, the site-specific surface response spectra with 5 percent damping are developed based on the mean plus one standard deviation concept from the result of local site effect analysis.